2018
DOI: 10.7454/hubs.asia.2130118
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and Confirmatory Factor Analysis of the Academic Motivation Scale (AMS)–Bahasa Indonesia

Abstract: Validity evidence based on internal structure is important for psychological measurements and this internal structure can be evaluated by factor analysis. Two types of factor analysis are often conducted on psychometric tests: confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). This study compared the groupings of the 30-item Indonesian version of the Academic Motivation Scale (AMS-Bahasa Indonesia), using both CFA and EFA. The CFA of the data sample from 1,168 undergraduates indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 28 publications
2
21
0
2
Order By: Relevance
“…e current study agrees with the study of Natalya and Purwanto [46] that was conducted in Indonesia and concluded that the items of the academic motivation scale were loaded on three dimensions: intrinsic motivation, extrinsic motivation, and Amotivation. e results partially agreed with those of several studies that did not confirm the sevenfactor model, such as that of Taghipour Ali Hosein et al [39] which concluded that the scale consists of two dimensions, and the study by Alruaili [66] concluded that the scale consists of four dimensions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…e current study agrees with the study of Natalya and Purwanto [46] that was conducted in Indonesia and concluded that the items of the academic motivation scale were loaded on three dimensions: intrinsic motivation, extrinsic motivation, and Amotivation. e results partially agreed with those of several studies that did not confirm the sevenfactor model, such as that of Taghipour Ali Hosein et al [39] which concluded that the scale consists of two dimensions, and the study by Alruaili [66] concluded that the scale consists of four dimensions.…”
Section: Discussionsupporting
confidence: 90%
“…Caleon et al [44] conducted a cross-cultural validation in Singapore; Zhang et al [45] conducted a validation of AMS in China. Natalya and Purwanto [46] conducted a validation of AMS in Indonesia. e factorial structure of the AMS was also verified in the Arab environment by Abu Awad [47], who aimed to examine the factorial structure of the academic motivation scale on a sample of sixth-and tenth-grade students in the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) schools in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequently used instruments in measuring motivation based on selfdetermination theory is the Academic Motivation Scale or AMS (Vallerand et al, 1992). Several existence studies in various countries such as France (Blanchard et al, 1997), Canada (Vallerand et al, 1992, the USA (Osei Akoto, 2014), Italy (Alivernini & Lucidi, 2008), Turkey (Can, 2015), Norway (Støen Utvaer & Haugan, 2016), and Indonesia (Marvianto & Widhiarso, 2019;Natalya & Purwanto, 2018;Wasityastuti et al, 2018) have proven the instrument's validity and reliability. AMS shows good reliability and validity tested on school (Alivernini & Lucidi, 2008;Bacanlı & Sahinkaya, 2011;Marvianto & Widhiarso, 2019;Støen Utvaer & Haugan, 2016) and college students (Orsini, 2015;Can, 2015;Osei Akoto, 2014;Natalya, 2018;Natalya & Purwanto, 2018;Vallerand et al, 1992;Wasityastuti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Bosato (2001) study adapted AMS by changing several sentences in the last version of AMS. Fruthermore, Natalya & Purwanto (2018) added two alternative items for the amotivation aspect because they considered that the addition of these items was important. Several studies on AMS adapted into Indonesian and published, such as AMS-30 and AMS-15 items for college students (Natalya & Purwanto, 2018) and AMS-28 items for high school students (Marvianto & Widhiarso, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation